Efficacy and safety of insulin degludec/aspart in patients with type 2 and type 1 diabetes mellitus: real-world evidence from Indonesia - Zufry, Hendra; Sucipto, Krishna Wardhana; Ekadamayanti, Agustia Sukri; Iqbal, Qanita (Frontiers in Endocrinology, 2025)
BackgroundReal-world studies on insulin degludec/aspart (IDegAsp) have been conducted in some Southeast Asian populations; however, data specific to Indonesia remain limited. The aim of this study was to evaluate the efficacy, safety profiles, and real-world clinical experience of IDegAsp after five years of implementation in diabetes care in Indonesia.MethodsThis five-year, single-center, open-label, prospective, non-interventional study included adults with type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) who had been on IDegAsp treatment for at least 12 months. Glycemic and metabolic outcomes—glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), postprandial glucose (PPG), and body mass index (BMI)—were assessed at baseline, 3, 6, and 12 months. The safety was evaluated based on hypoglycemia incidence. Clinical rationale for IDegAsp initiation and regimen models were also documented.ResultsA total of 550 individuals (T1DM: 48; T2DM: 502) were included. At 12 months, both groups had significant reductions in HbA1c (T1DM: −3.60%, T2DM: −3.32%), FPG (T1DM: −119.39 mg/dL, T2DM: −105.60 mg/dL), and PPG (T1DM: −190.87 mg/dL, T2DM: −180.10 mg/dL) (all p < 0.001 compared to baseline). Slight but statistically significant increases in BMI were observed in both groups (both p < 0.001). No episodes of hypoglycemia were reported among T1DM patients, whereas in the T2DM cohort, it occurred in 3.0% of cases comprising 1.4% with a single episode and 1.6% with two episodes with no severe hypoglycemia reported. The most frequent reasons for initiating IDegAsp included suboptimal HbA1c and PPG levels, with T2DM patients more often citing the need for flexible injection time or schedule.ConclusionIDegAsp demonstrated sustained glycemic improvement at 3-, 6-, and 12-months follow-ups with a favorable safety profile over one year, in both T1DM and T2DM populations in Indonesia. These findings support its utility in routine clinical practice, particularly among patients with unmet glycemic targets or complex treatment needs.